PENGARUH KESELAMATAN DAN KESEHATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT SIMATELEX MANUFACTORY BATAM - Siregar, Mia Oktaviani; Daris Purba (LPPM Universitas Putera Batam, 2021)
ABSTRACT Human resources are one of the resources that determine the success or failure of an organization. Companies that have effective and efficient human resources will make the company progress and develop. In the current era, companies are required to work harder and more efficiently in increasing competitiveness for the survival of the company. The company will strive to maximize employees to get company benefits and values, so as to improve the welfare of owners and employees. The purpose of this study was to analyze the effect of occupational safety and health and work environment simultaneously on employee performance at PT Simatelex Manufactory Batam. The population in this study were employees of PT Simatelex Manufactory Batam. The number of samples in this study was 100 using non propobability sampling technique. The data analysis technique in this research is using multiple linear regression analysis, classical assumption test, statistical test. The results showed, among others: (1) occupational safety and health has an effect on employee performance; (2) work environment has an effect on employee performance; (3) showing that of occupational safety and health and work environment simultaneously affect employee performance. Keywords: Employee Performance; Occupational Safety and Health; Work Environment